Optımızation of bio-based coating systems containing eucalyptus oil, linseed oil, and boric acid for iron surface protection - Yavuzarslan, Sevval Ecem; Acarali, Nil (TAYLOR & FRANCIS INC, 2026)
This study investigated the development of environmentally friendly coating formulations for iron surfaces using natural additives, including eucalyptus oil, linseed oil, and boric acid. The formulations were optimized using Design-Expert software to enhance corrosion resistance and surface-related properties. Corrosion performance was assessed through salt exposure tests and electrochemical measurements, where Electrochemical Impedance Spectroscopy (EIS) demonstrated a significant improvement in corrosion resistance compared to the reference water-based coating. Water repellency was enhanced, with contact angle values increasing from 65 degrees for the reference coating to 76 degrees for the optimized formulation. Thermal behavior evaluated by TG-DTA analysis showed that the optimized coating exhibited improved thermal stability, retaining 62.24% residual mass with a total mass loss of 37.72% at 623 degrees C, whereas the reference coating displayed considerably lower thermal resistance. Additional analyses, including color measurements, physical tests, and SEM observations, confirmed improvements in surface morphology and barrier integrity. Overall, the incorporation of natural and boron-based additives effectively enhanced the corrosion resistance, thermal stability, and surface performance of the coating, providing a sustainable approach for protecting iron surfaces.
Keywords: Coating; iron surface; environmentally friendly; corrosion; eucalyptus oil; boric acid; DEGRADATION; Engineering